Extraction of calcium oxalate from sliced palauan (Cyrtosperma merkusii) corm - Pama, Shem P.
palauan (Cyrtosperma merkusii) is a minor root crop in the Philippines with limited commercial use because of its inherent acridity that may be associated to its calcium oxalate content.